Model Regulasi Emosi, Efikasi Diri, dan Learning Agility pada Guru Pembimbing Khusus di Sekolah Inklusi Muhammadiyah Sidoarjo - Laili, Nurfi; Affandi, Ghozali Rusyid; Widyastuti, Widyastuti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to develop a learning agility model for special mentor teachers in terms of its relationship with self-efficacy and emotion regulation. This study uses correlational quantitative methods with correlation and regression analysis types by making self-efficacy and emotion regulation as independent variables and learning agility as the dependent variable. The population of this study was special supervising teachers in Muhammadiyah inclusive schools in Sidoarjo Regency aged 20-40 years with a total of 50 people taken through saturated sampling technique. The measuring instruments used in this study amounted to 3 psychological scales, including: adaptation of the Learning Agility scale, adaptation of General Self Efficacy to determine the self-efficacy of special mentor teachers, and to determine the emotion regulation of special mentor teachers using adaptation of the Emotion Regulation Scale. This study concluded that there is a significant relationship between self-efficacy and learning agility (rxx' = 0.345, p = 0.014 <0.05). Meanwhile, emotion regulation did not find a significant relationship with learning agility (rxx' = 0.183, p = 0.203>0.05). The regression analysis results show that f count = 3.210 (p = 0.049<0.05), this value indicates that the hypothesis is accepted. This means that together self-efficacy and emotion regulation have a significant influence on learning agility. However, the influence of the two variables, which is self-efficacy and emotion regulation, is only able to predict 12% of learning agility.